ETNOMATEMATIKA PADA PERMAINAN TRADISIONAL ENGKLEK BESERTA ALATNYA SEBAGAI BAHAN AJAR - Aprilia, Erly Dwi; Trapsilasiwi, Dinawati; Setiawan, Toto Bara (Kadikma, 2019)
The purpose of this study is to describe ethnomatematic of engklek (Javanese traditional game). This research also to create teaching materials in the form student’s worksheet. This type of research is qualitative research with ethnographic approaches. The data collection methods used are observations, interviews, and documentation. The object of this research is engklek (Javanese traditional game) with the speaker by head of Cultural division from Department of Education and Culture in Bondowoso district. Based on the results of this study, it can be noted that engklek (Javanese traditional game) has mathematical elements. The mathematical elements that found are planes, counting, nets, congruent, reflection, opportunity, and mathematical logic. This research focuses on several objects, including the tile, players, gaco, and the rules of the game. The tiles contain planes, reflections, congruent, nets, and counting. Players of engklek contain counting and opportunity. Gaco from engklek (Javanese traditional game) contain planes, meanwhile rules of the game contain mathematical logic. The teaching materials obtained in this study are the worksheets of students with the material planes for class VIII and the material congruent for class IX. Keywords: Ethnomatematics, Engklek (Javanese Traditional Game), Geometry